Laminate, optical component, imprint method, and method for manufacturing optical component
The laminate structure with a glass layer and a resin layer having a thickness ratio less than 0.9 addresses the warping issues in optical components by providing enhanced dimensional stability and impact resistance.
Patent Information
- Application Number
- JP2023168647
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
AI Technical Summary
Existing optical components, such as those used in display elements and solar cells, face issues with warping due to curing shrinkage of UV-curable resins on resin substrates and thermal expansion of resin substrates during use.
A laminate structure comprising a glass layer and a resin layer, where the ratio of the average thickness of the resin layer to the average thickness of the glass layer is less than 0.9, is introduced to suppress warping.
The laminate effectively suppresses warping, particularly caused by heating, while maintaining suitable bending properties and impact resistance, making it suitable for use as a substrate in nanoimprinting and other optical components.
Smart Images

Figure 2025058609000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate, an optical component, an imprint method, and a method for manufacturing an optical component. [Background technology]
[0002] In recent years, display elements such as flat panel displays (FPDs; for example, liquid crystal display elements, organic EL display elements, etc.) and solar cells have been becoming lighter and thinner from the viewpoints of transportability, storage, design, etc., and there is also a demand for improved flexibility. Conventionally, glass substrates have been used in many transparent laminates used in display elements and solar cells. Glass substrates are excellent in transparency, solvent resistance, gas barrier properties, and heat resistance. However, when the glass material constituting the glass substrate is made lighter and thinner, it exhibits a certain degree of flexibility but is not sufficient, and the impact resistance is insufficient, resulting in problems such as difficult handling.
[0003] In order to improve the handleability of thin glass substrates, substrates in which a resin layer is formed on the glass surface have been disclosed (see, for example, Patent Document 1). However, even with the use of these techniques, a laminate exhibiting sufficient dimensional stability and flexibility has not yet been obtained.
[0004] Meanwhile, nanoimprint technology used in display elements such as flat panel displays (FPDs; e.g., liquid crystal display elements, organic electroluminescence display elements, etc.) and solar cells is a method of transferring nanometer to micrometer sized parts, which are impossible to achieve by injection molding, to a substrate using a mold, and there are two types of nanoimprinting: UV (Ultra-Violet) nanoimprinting and thermal nanoimprinting. UV nanoimprinting is a method in which UV curable resin poured into a mold is irradiated with UV light to harden the UV curable resin and form it, while thermal nanoimprinting is a method in which thermoplastic resin poured into a mold is molded by applying heat and pressure. UV nanoimprinting has a short curing time of just a few seconds, making it a highly productive method.
[0005] For example, when manufacturing optical components by the UV nanoimprint method, a method has been proposed in which a photosensitive resin layer such as a UV-curable resin is formed on a resin substrate such as a polyethylene terephthalate (PET) film, and the photosensitive resin layer is exposed to light through a mask pattern to harden it, thereby forming a molded body on the resin substrate (see Patent Document 2). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 11-329715 [Patent Document 2] WO 01 / 22165 Summary of the Invention [Problem to be solved by the invention]
[0007] The optical members described in Patent Documents 1 and 2 have problems in that the molded product is warped due to, for example, cure shrinkage that occurs when the UV-curable resin on a resin substrate such as a PET film is cured, and expansion and contraction of the resin substrate due to application of heat during use.
[0008] An object of the embodiments of the present invention is to provide a laminate capable of solving the above-mentioned problems in the conventional art and suppressing warping. [Means for solving the problem]
[0009] One embodiment of the present invention is a laminate comprising a glass layer and a resin layer disposed on at least one surface of the glass layer, wherein the ratio of an average thickness of the resin layer to an average thickness of the glass layer (resin layer / glass layer) is less than 0.9. Effect of the Invention
[0010] The embodiment of the present invention can provide a laminate capable of suppressing warpage. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a laminate according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another example of the laminate according to the embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing another example of the laminate according to the embodiment of the present invention. [Figure 4] FIG. 4 is a schematic cross-sectional view showing another example of the laminate according to the embodiment of the present invention. [Diagram 5] FIG. 5 is a schematic cross-sectional view showing another example of the laminate according to the embodiment of the present invention. [Figure 6] FIG. 6 is a schematic top view illustrating a measurement method when the distortion of the laminate in the embodiment of the present invention is measured by digital image correlation analysis (DIC analysis). [Figure 7A] FIG. 7A is an explanatory diagram showing an example of a speckle pattern on the exposed surface (upper surface) of the resin layer of a laminate before heating when the distortion of the laminate in an embodiment of the present invention is measured by digital image correlation analysis (DIC analysis). [Figure 7B] FIG. 7B is an explanatory diagram showing an example of a speckle pattern after heating on the exposed surface (upper surface) of the resin layer of the laminate when the distortion of the laminate in an embodiment of the present invention is measured by digital image correlation analysis (DIC analysis). [Figure 8] FIG. 8 is a photograph showing the distortion of the laminates of Examples 1 to 5 and Comparative Example 1 after heating, measured by a digital image correlation method (DIC analysis), using a color meter. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the embodiments of the present invention will be described in detail. Note that the embodiments are not limited by the following description, and can be appropriately modified without departing from the gist of the present invention. In addition, in this specification, "to" indicating a numerical range means that the numerical values before and after it are included as the lower and upper limits, unless otherwise specified.
[0013] In addition, when describing the embodiments of the present invention with reference to the drawings, the same components in each drawing may be given the same reference numerals, and duplicated descriptions may be omitted. Furthermore, the number, position, size, shape, etc. of components are not limited to the embodiments of the present invention, and may be the number, position, size, shape, etc. that are preferable for implementing the present invention.
[0014] (Laminate) The laminate in the embodiment of the present invention has a glass layer and a resin layer disposed on at least one surface of the glass layer, and further has other layers as necessary. In the laminate in the embodiment of the present invention, the ratio of the average thickness of the resin layer to the average thickness of the glass layer (resin layer / glass layer) is less than 0.9. This allows the laminate in the embodiment of the present invention to suppress warping, and in particular, to suitably suppress warping due to heating.
[0015] [Average thickness ratio (resin layer / glass layer)] In the laminate according to the embodiment of the present invention, the ratio of the average thickness of the resin layer to the average thickness of the glass layer (resin layer / glass layer) is less than 0.9, preferably 0.5 or less, more preferably 0.4 or less, and even more preferably 0.3 or less. If the average thickness ratio (resin layer / glass layer) is 0.9 or more, the laminate will warp. On the other hand, if the average thickness ratio (resin layer / glass layer) is less than 0.9, the laminate will not warp and will have good flexibility.
[0016] In the embodiment of the present invention, the "average thickness of the glass layer" and the "average thickness of the resin layer" mean the sum of the average thicknesses of the multiple layers (total thickness) when the glass layer and the resin layer are multilayered.
[0017] In this embodiment, the "average thickness" refers to the average value of thicknesses at three points arbitrarily selected from the target layer. The thickness of each layer can be measured using a known film thickness measuring device (e.g., R1-205, PEACOCK (registered trademark) (Ozaki Manufacturing Co., Ltd.)).
[0018] [Suppression of warpage] The suppression of warpage of the laminate in the embodiment of the present invention is measured by digital image correlation (DIC analysis). Specifically, a spray paint generally used in DIC analysis (e.g., water-based lacquer spray, manufactured by Sunday Paint Co., Ltd.) is spray-coated on the exposed surface of the resin layer of the laminate in the embodiment of the present invention, and a random granular pattern (hereinafter sometimes referred to as "speckle pattern") is applied to the exposed surface of the resin layer of the laminate. The z-direction strain of the laminate is calculated from the change in the speckle pattern before and after heating the laminate at 60°C.
[0019] FIG. 7A is an explanatory diagram showing an example of a speckle pattern before heating on the exposed surface (upper surface) of the resin layer of the laminate when the distortion of the laminate in the embodiment of the present invention is measured by DIC analysis. FIG. 7B is an explanatory diagram showing an example of a speckle pattern after heating on the exposed surface (upper surface) of the resin layer of the laminate when the distortion of the laminate in the embodiment of the present invention is measured by DIC analysis. Points A and B in FIG. 7A respectively indicate adjacent points of the speckle pattern. The distance between points A and B is D. Points A and B' in FIG. 7B indicate adjacent points of the speckle pattern after heating, and indicate that, when point A in FIG. 7A is taken as the starting point, point B has moved to the position of point B' in FIG. 7B due to the expansion of the resin layer. The distance between points A and B' is D'. When distortion occurs in the resin layer of the laminate after heating, expansion or contraction occurs in the x direction and y direction on the exposed surface (upper surface) of the resin layer. When the resin layer of the laminate expands due to heating (i.e., distance D<distance D'), the resin layer of the laminate warps, and the position of point B in FIG. 7A moves to the position of point B' in FIG. 7B. Therefore, the distance D before heating moves away from the distance D' after heating. Thus, the distortion of the laminate in the embodiment of the present invention can be calculated based on the following formula (1). In addition, when the resin layer of the laminate shrinks due to heating (i.e., distance D>distance D'), the movement direction of point B' moves toward point A' on D shown by a straight line, and in this case as well, the distortion of the laminate in the embodiment of the present invention can be calculated based on the following formula (1). In addition, the x direction and the y direction both indicate directions perpendicular to the thickness direction of the laminate. The x direction and the y direction may be the machine direction of the resin of the resin layer (also called the "flow direction" or "MD direction"), or may be a direction perpendicular to the MD direction (also called the "width direction" or "TD direction"). Distortion (%) = ΔD / D × 100 Equation (1)
[0020] Next, the amount of displacement in the z direction is calculated from the strain calculated based on formula (1). In the embodiment of the present invention, the z direction means a direction perpendicular to the plane consisting of the x direction and the y direction, that is, the thickness direction of the laminate in the embodiment of the present invention. FIG. 6 is a schematic top view for explaining a measurement method when measuring the strain of the laminate in the embodiment of the present invention by DIC analysis. As shown in FIG. 6, the surface on which a speckle pattern is applied (the area shown by the solid line in FIG. 6) is divided into nine parts as shown by the dotted line in FIG. 6, and the maximum value of the displacement in the z direction in each of the nine divided parts is calculated at nine points, and the maximum value among the maximum values of the displacement in the z direction at the nine points is set as the maximum z displacement of the measurement sample at 60°C. The "maximum z displacement" calculated in this way is set as the "maximum thermal warpage" in the embodiment of the present invention. The larger the maximum thermal warpage, the larger the thermal warpage of the laminate. The strain in the x direction and the y direction, and the displacement in the z direction can be measured using a known deformation measurement and strain analysis device (for example, StarinMaster, manufactured by LaVision).
[0021] The absolute value of the maximum thermal warpage in the thickness direction of the laminate in the embodiment of the present invention at 60° C. when measured by a digital image correlation method is not particularly limited and can be appropriately selected depending on the purpose, but is preferably less than 2 mm, more preferably 0.5 mm or less, even more preferably 0.3 mm or less, and particularly preferably 0.1 mm or less. When the absolute value of the maximum thermal warpage in the thickness direction of the laminate is less than 2 mm, the laminate in the embodiment of the present invention can be suitably used as a substrate for imprinting.
[0022] Thickness The average thickness of the laminate in the embodiment of the present invention is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 80 μm to 130 μm. In addition, in the embodiment of the present invention, the average thickness of the laminate means the sum of the average thicknesses of all layers in the laminate in the embodiment of the present invention (total thickness). In the laminate in the embodiment of the present invention, the resin layer can make the thickness of the glass layer significantly thinner than that of a conventional glass substrate. That is, even if the resin layer is thin, it can contribute to improving impact resistance and toughness, so the laminate in the embodiment of the present invention having the resin layer is lightweight, thin, has excellent impact resistance, and can suppress warping.
[0023] [Light transmittance] The light transmittance of the laminate in the embodiment of the present invention at a wavelength of 550 nm is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The light transmittance of the laminate at a wavelength of 550 nm can be measured by a spectrophotometer (e.g., U-4100, manufactured by Hitachi, Ltd.).
[0024] Furthermore, the laminate in the embodiment of the present invention preferably has a loss in light transmittance of 5% or less after being subjected to a heat treatment for 2 hours at 180° C. With such a loss, a practically acceptable light transmittance can be suitably ensured even if a heat treatment required in the imprint process is performed.
[0025] [Surface roughness Ra] The surface roughness Ra of the laminate in the embodiment of the present invention (substantially, the surface roughness Ra of the resin layer or other layers) is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 50 nm or less, more preferably 30 nm or less, and even more preferably 10 nm or less.
[0026] [Linear expansion coefficient] The linear expansion coefficient of the laminate in the embodiment of the present invention is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 15 ppm / °C or less, more preferably 10 ppm / °C or less, and even more preferably 1 ppm / °C to 10 ppm / °C. The laminate in the embodiment of the present invention has a glass layer, and therefore exhibits excellent dimensional stability (for example, a linear expansion coefficient in the above range). More specifically, in addition to the rigidity of the glass layer itself, the resin layer is restrained by the glass layer, and thus the dimensional fluctuation of the resin layer can also be suppressed. As a result, the laminate as a whole exhibits excellent dimensional stability and warpage is suppressed.
[0027] <Glass layer> The material constituting the glass layer in the laminate in the embodiment of the present invention is not particularly limited, but is preferably inorganic glass.
[0028] The classification of the inorganic glass according to the composition is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include soda-lime glass, borate glass, aluminosilicate glass, quartz glass, etc. These may be used alone or in combination of two or more kinds.
[0029] In addition, the classification of inorganic glass based on the alkali component is not particularly limited and may be appropriately selected depending on the purpose. For example, alkali-free glass, low-alkali glass, etc. may be mentioned.
[0030] Examples of alkali metal components in inorganic glass include Na2O, KO, Li2O, etc. The content of the alkali metal component in inorganic glass is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 15 mass % or less, more preferably 10 mass % or less, based on the total mass of the inorganic glass.
[0031] The shape of the glass layer is not particularly limited and may be appropriately selected from any shape, but a plate shape is preferable.
[0032] In the laminate according to the embodiment of the present invention, the glass layer may be a single layer or a multilayer body, but is preferably a single layer.
[0033] The average thickness of the glass layer is not particularly limited as long as the average thickness ratio (resin layer / glass layer) is less than 0.9, and can be appropriately selected depending on the purpose, but is preferably less than 200 μm, more preferably 20 μm to 200 μm, and even more preferably 50 μm to 100 μm. Since the laminate in the embodiment of the present invention has a resin layer on at least one surface of the glass layer, when the thickness of the glass layer is 200 μm or less, the laminate can be given suitable flexibility, and when the thickness is 20 μm or more, the laminate can be given suitable impact resistance.
[0034] The light transmittance of the glass layer at a wavelength of 550 nm is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 85% or more, more preferably 90% or more, and even more preferably 95% or more. The light transmittance of the glass layer at a wavelength of 550 nm can be measured by a spectrophotometer (e.g., U-4100, manufactured by Hitachi, Ltd.).
[0035] The method for forming the glass layer is not particularly limited and can be appropriately selected depending on the purpose. For example, a glass layer made of inorganic glass can be formed by melting a mixture containing a main raw material such as silica or alumina, an antifoaming agent such as mirabilite or antimony oxide, and a reducing agent such as carbon at a temperature of 1,400°C to 1,600°C, forming it into a thin plate, and then cooling it to form it. The method for forming the glass layer into a thin plate (for example, 200 μm or less) is not particularly limited and can be appropriately selected depending on the purpose. For example, a slot downdraw method, a fusion method, a float method, etc. can be used. The glass layer formed into a plate by these methods may be chemically polished with a solvent such as hydrofluoric acid as necessary to make it thinner or to increase the smoothness. The glass layer may also be surface-treated.
[0036] The glass layer may be a commercially available product as it is, or may be a commercially available inorganic glass that has been polished to a desired thickness. Examples of commercially available inorganic glass include 7059, 1737, EAGLE2000 (all manufactured by Corning Incorporated), AN100 (manufactured by Asahi Glass Co., Ltd.), NA-35 (manufactured by NH Techno Glass Co., Ltd.), OA-10G (manufactured by Nippon Electric Glass Co., Ltd.), D263 (registered trademark), and AF45 (registered trademark) (all manufactured by Schott Corporation).
[0037] <Resin layer> The material constituting the resin layer in the laminate according to an embodiment of the present invention is not particularly limited as long as it contains a resin, and can be appropriately selected depending on the purpose. If necessary, it may further contain other components.
[0038] <<Resin>> The resin contained in the resin layer is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include thermoplastic resins and curable resins that are cured by heat or active energy rays. These may be used alone or in combination of two or more. Among these, it is preferable that the resin layer contains a thermoplastic resin.
[0039] Specific examples of resins contained in the resin layer include polyethersulfone-based resins; polycarbonate-based resins; epoxy-based resins; acrylic-based resins; polyester-based resins such as polyethylene terephthalate and polyethylene naphthalate; polyolefin-based resins; cycloolefin-based resins such as norbornene-based resins; polyimide-based resins; polyamide-based resins; polyimideamide-based resins; polyarylate-based resins; polysulfone-based resins; polyetherimide-based resins, and the like.
[0040] Among these, it is preferable that the resin layer contains at least one selected from the group consisting of a thermoplastic resin (A) having at least one repeating unit selected from the group consisting of a repeating unit represented by the following general formula (1) and a repeating unit represented by the following general formula (2), a thermoplastic resin (B) having one or more repeating units represented by the following general formula (3), and a thermoplastic resin (C) having a hydroxyl group at a terminal.
[0041] -Thermoplastic resin (A)- The thermoplastic resin (A) is a thermoplastic resin having at least one repeating unit selected from the group consisting of a repeating unit represented by the following general formula (1) and a repeating unit represented by the following general formula (2). By containing the thermoplastic resin (A), a resin layer having excellent adhesion to other layers (e.g., coupling agent layer, adhesive layer, etc.) in contact with the glass layer or the resin layer and excellent toughness can be obtained. As a result, a laminate in which cracks are unlikely to develop when cut can be obtained. In addition, the thermoplastic resin (A) having excellent adhesion to other layers in contact with the glass layer or the resin layer is strongly bound to the glass layer, and dimensional fluctuations are reduced. As a result, a laminate having a resin layer containing the thermoplastic resin (A) exhibits excellent dimensional stability and more suitably suppresses warping.
[0042] [ka] In the general formula (1), R 1 represents a substituted or unsubstituted aromatic hydrocarbon group having 6 to 24 carbon atoms, an alicyclic hydrocarbon group having 4 to 14 carbon atoms, or a linear or branched aliphatic hydrocarbon group having 1 to 8 carbon atoms; R 2 represents a substituted or unsubstituted aromatic hydrocarbon group having 6 to 24 carbon atoms, a linear or branched aliphatic hydrocarbon group having 1 to 8 carbon atoms, an alicyclic hydrocarbon group having 5 to 12 carbon atoms, or a hydrogen atom.
[0043] In the general formula (1), R 1is preferably a substituted or unsubstituted aromatic hydrocarbon group having 6 to 20 carbon atoms, an alicyclic hydrocarbon group having 4 to 12 carbon atoms, or a linear or branched aliphatic hydrocarbon group having 1 to 6 carbon atoms, and more preferably a substituted or unsubstituted aromatic hydrocarbon group having 6 to 18 carbon atoms, an alicyclic hydrocarbon group having 5 to 10 carbon atoms, or a linear or branched aliphatic hydrocarbon group having 1 to 4 carbon atoms.
[0044] In the general formula (1), R 2 is preferably a substituted or unsubstituted aromatic hydrocarbon group having 6 to 20 carbon atoms, a linear or branched aliphatic hydrocarbon group having 1 to 6 carbon atoms, an alicyclic hydrocarbon group having 5 to 10 carbon atoms, or a hydrogen atom.
[0045] [ka]
[0046] In the general formula (2), R 3 and R 4 each independently represents a linear or branched aliphatic hydrocarbon group having 1 to 8 carbon atoms, a hydrogen atom, or an alicyclic hydrocarbon group having 5 to 12 carbon atoms, A represents a carbonyl group or a linear or branched aliphatic hydrocarbon group having 1 to 8 carbon atoms, m represents an integer of 0 to 8, and n represents an integer of 0 to 4. Here, "each independently" means that R 3 and R 4 This means that they may be the same or different.
[0047] In the general formula (2), R 3 and R 4 are each independently preferably a linear or branched aliphatic hydrocarbon group having 1 to 5 carbon atoms, a hydrogen atom, or an alicyclic hydrocarbon group having 5 to 10 carbon atoms, and more preferably a linear or branched aliphatic hydrocarbon group having 1 to 4 carbon atoms, a hydrogen atom, or an alicyclic hydrocarbon group having 5 to 8 carbon atoms.
[0048] In formula (2), A is preferably a carbonyl group or a linear or branched aliphatic hydrocarbon group having 1 to 6 carbon atoms, and more preferably a carbonyl group or a linear or branched aliphatic hydrocarbon group having 1 to 4 carbon atoms.
[0049] In formula (2), m is preferably an integer of 0 to 6, and more preferably an integer of 0 to 3.
[0050] In the general formula (2), n is preferably an integer of 0 to 2.
[0051] The degree of polymerization of the thermoplastic resin (A) is not particularly limited and can be appropriately selected depending on the purpose, but is preferably from 10 to 6,000, more preferably from 20 to 5,000, and even more preferably from 50 to 4,000.
[0052] Specific examples of the thermoplastic resin (A) include styrene-maleic anhydride copolymer, ester group-containing cycloolefin polymer, etc. These may be used alone or in combination of two or more.
[0053] -Thermoplastic resin (B)- The thermoplastic resin (B) is a thermoplastic resin having one or more repeating units represented by the following general formula (3). By containing the thermoplastic resin (B) in the resin layer, it is possible to obtain a resin layer that has excellent adhesion to the glass layer or other layers in contact with the resin layer (e.g., coupling agent layer, adhesive layer, etc.) and also has excellent toughness. As a result, it is possible to obtain a laminate in which cracks are unlikely to develop when cut. In addition, the thermoplastic resin (B) having excellent adhesion to the glass layer or other layers in contact with the resin layer is strongly bound by the glass layer, and dimensional fluctuations are reduced. As a result, a laminate having a resin layer containing the thermoplastic resin (B) exhibits excellent dimensional stability and more suitably suppresses warping.
[0054] [ka] In the general formula (3), R 5represents a substituted or unsubstituted aromatic hydrocarbon group having 6 to 24 carbon atoms, a linear or branched aliphatic hydrocarbon group having 1 to 8 carbon atoms, an alicyclic hydrocarbon group having 4 to 14 carbon atoms, or an oxygen atom; R 6 represents a substituted or unsubstituted aromatic hydrocarbon group having 6 to 24 carbon atoms, a linear or branched aliphatic hydrocarbon group having 1 to 8 carbon atoms, an alicyclic hydrocarbon group having 5 to 12 carbon atoms, or a hydrogen atom,
[0055] In the general formula (3), R 5 is preferably a substituted or unsubstituted aromatic hydrocarbon group having 6 to 20 carbon atoms, a linear or branched aliphatic hydrocarbon group having 1 to 6 carbon atoms, an alicyclic hydrocarbon group having 4 to 12 carbon atoms, or an oxygen atom, and more preferably a substituted or unsubstituted aromatic hydrocarbon group having 6 to 18 carbon atoms, a linear or branched aliphatic hydrocarbon group having 1 to 4 carbon atoms, an alicyclic hydrocarbon group having 5 to 10 carbon atoms, or an oxygen atom.
[0056] In the general formula (3), R 6 is preferably a substituted or unsubstituted aromatic hydrocarbon group having 6 to 20 carbon atoms, a linear or branched aliphatic hydrocarbon group having 1 to 6 carbon atoms, an alicyclic hydrocarbon group having 5 to 10 carbon atoms, or a hydrogen atom.
[0057] The degree of polymerization of the thermoplastic resin (B) is not particularly limited and can be appropriately selected depending on the purpose, but is preferably from 10 to 6,000, more preferably from 20 to 5,000, and even more preferably from 50 to 4,000.
[0058] Specific examples of the thermoplastic resin (B) include polyarylates, polyesters, polycarbonates, etc. These may be used alone or in combination of two or more.
[0059] -Thermoplastic resin (C)- The thermoplastic resin (C) is a thermoplastic resin having a hydroxyl group at its terminal. The thermoplastic resin (C) is suitably used when the laminate has a coupling agent layer formed by an epoxy group-terminated coupling agent.
[0060] Specific examples of the thermoplastic resin (C) include thermoplastic resins obtained by modifying polyimide, polyimideamide, polyethersulfone, polyetherimide, polysulfone, polyarylate, polycarbonate, etc. with terminal hydroxyl groups. These may be used alone or in combination of two or more. By using such a thermoplastic resin (C), a resin layer having excellent adhesion to the coupling agent layer formed by the epoxy group-terminated coupling agent and excellent toughness can be obtained. As a result, a laminate in which cracks are unlikely to develop when cut can be obtained. In addition, the thermoplastic resin (C) having excellent adhesion to the coupling agent layer formed by the epoxy group-terminated coupling agent is strongly bound to the glass layer, and dimensional fluctuations are reduced. As a result, a laminate having a resin layer containing the thermoplastic resin (C) exhibits excellent dimensional stability and more suitably suppresses warpage. Any appropriate method can be used for the modification of terminal hydroxyl groups. Details of the epoxy group-terminated coupling agent will be described later.
[0061] The degree of polymerization of the thermoplastic resin (C) is not particularly limited and can be appropriately selected depending on the purpose, but is preferably from 90 to 6,200, more preferably from 130 to 4,900, and even more preferably from 150 to 3,700.
[0062] The weight average molecular weight of the thermoplastic resin (C) is not particularly limited and can be appropriately selected depending on the purpose. However, it is preferable that the weight average molecular weight is 2.0×10 in terms of polyethylene oxide. 4 ~150×10 4 is preferred, 3×10 4 ~120×10 4 is more preferable, and 3.5×10 4 ~90×10 4 The weight average molecular weight of the thermoplastic resin (C) is more preferably 2.0×10 4 If the thickness is more than 150×10, the resin layer has a sufficient toughness and the glass layer can be reinforced. 4 When the viscosity is not more than this, the viscosity does not become too high and the handling properties are good.
[0063] The terminal hydroxyl group of the thermoplastic resin (C) is not particularly limited and can be appropriately selected according to the purpose, but a phenolic hydroxyl group is preferable. When the thermoplastic resin (C) having a phenolic hydroxyl group is contained, the resin layer and the coupling agent layer formed by the epoxy group-terminated coupling agent can be firmly adhered to each other.
[0064] The content of terminal hydroxyl groups in the thermoplastic resin (C) is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.3 or more, more preferably 0.5 to 2.0, per 100 degrees of polymerization of the thermoplastic resin (C). When the content of terminal hydroxyl groups in the thermoplastic resin (C) is 0.3 or more per 100 degrees of polymerization of the thermoplastic resin (C), a thermoplastic resin having excellent reactivity with an epoxy group-terminated coupling agent can be obtained.
[0065] <<Other ingredients>> Other components in the resin layer are not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include various additives such as diluents, antioxidants, modifiers, surfactants, dyes, pigments, discoloration inhibitors, UV absorbers, softeners, stabilizers, plasticizers, defoamers, reinforcing agents, etc. The types, numbers, and amounts of additives contained in the resin layer are not particularly limited and can be appropriately selected depending on the purpose.
[0066] In addition, when the resin layer contains the thermoplastic resin (C), it is preferable that the resin layer further contains at least one selected from the group consisting of imidazoles, epoxies, and oxetanes. When the resin layer contains at least one selected from the group consisting of imidazoles, epoxies, and oxetanes, the resin layer and the glass layer having the epoxy group-terminated coupling agent layer can be stably adhered to each other, so that the laminate can be obtained with a high yield.
[0067] -Imidazoles- Examples of imidazoles include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, epoxyimidazole adduct, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazo , 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, etc. These may be used alone or in combination of two or more.
[0068] The content of the imidazoles is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5 mass % to 5 mass %, and more preferably 1 mass % to 4 mass %, based on the total mass of the thermoplastic resin (C).
[0069] -Epoxies- The epoxy resins are not particularly limited as long as they have an epoxy group in the molecule, and examples thereof include bisphenol types such as bisphenol A type, bisphenol F type, bisphenol S type, or water additives thereof; novolac types such as phenol novolac type and cresol novolac type; nitrogen-containing ring types such as triglycidyl isocyanurate type and hydantoin type; alicyclic type; aliphatic type; aromatic type such as naphthalene type and biphenyl type; glycidyl type such as glycidyl ether type, glycidyl amine type and glycidyl ester type; dicyclo type such as dicyclopentadiene type; ester type; ether ester type; and modified types thereof. These may be used alone or in combination of two or more types. Among these, the epoxy resins are preferably bisphenol A type epoxy resin, alicyclic type epoxy resin, nitrogen-containing ring type epoxy resin, or glycidyl type epoxy resin.
[0070] The content of the epoxy compounds is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 mass % to 15 mass %, and more preferably 3 mass % to 10 mass %, based on the total mass of the thermoplastic resin (C).
[0071] -Oxetanes- The oxetanes are not particularly limited and can be appropriately selected depending on the purpose. However, at least one selected from the group consisting of a compound represented by the following general formula (4), a compound represented by the following general formula (5), and a compound represented by the following general formula (6) is preferable.
[0072] [ka] In the general formula (4), R 7 represents a hydrogen atom, an alicyclic hydrocarbon group, a phenyl group, a naphthyl group, or an aliphatic hydrocarbon group having 1 to 10 carbon atoms.
[0073] [ka]
[0074] [ka]
[0075] In the general formula (6), R 8 represents an alicyclic hydrocarbon group, a phenyl group, a naphthyl group or an aliphatic hydrocarbon group having 1 to 10 carbon atoms. p represents an integer of 1 to 5.
[0076] Specific examples of oxetanes include 3-ethyl-3-hydroxymethyloxetane (oxetane alcohol), 2-ethylhexyloxetane, xylylene bisoxetane, 3-ethyl-3(((3-ethyloxetan-3-yl)methoxy)methyl)oxetane, etc. These may be used alone or in combination of two or more.
[0077] The content of the oxetanes is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5% by mass to 10% by mass, and more preferably 1% by mass to 5% by mass, based on the total mass of the thermoplastic resin (C).
[0078] The resin layer may be a single layer or a multilayer body. In one embodiment, the resin layer is a multilayer body having a layer containing a thermoplastic resin (A) and a layer containing a thermoplastic resin not having the repeating units represented by general formula (1) and general formula (2). In another embodiment, the resin layer is a multilayer body having a layer containing a thermoplastic resin (B) and a layer containing a thermoplastic resin not having the repeating units represented by general formula (3). When the resin layer is such a multilayer body, a laminate having better mechanical strength and heat resistance can be obtained.
[0079] The glass transition temperature (Tg) of the resin contained in the resin layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 150° C. to 350° C., more preferably 180° C. to 320° C., and even more preferably 210° C. to 290° C. When the glass transition temperature (Tg) of the resin contained in the resin layer is 150° C. to 350° C., a laminate having excellent heat resistance can be obtained.
[0080] The resin layer preferably further has chemical resistance. Specifically, the resin layer preferably has chemical resistance to solvents used in the cleaning step, resist stripping step, etc. in the imprint process. Examples of the solvents used in the cleaning step, etc. in the imprint process include isopropyl alcohol, acetone, dimethyl sulfoxide (DMSO), and N-methylpyrrolidone (NMP).
[0081] The average thickness of the resin layer is not particularly limited as long as the ratio of the average thickness (resin layer / glass layer) is less than 0.9, and can be appropriately selected according to the purpose, but is preferably less than 180 μm, more preferably 5 μm to 100 μm, even more preferably 5 μm to 40 μm, and particularly preferably 5 μm to 30 μm. When the average thickness of the resin layer is less than 180 μm, warping of the laminate can be suitably suppressed. When the resin layer is disposed on both sides of the glass layer or is made of multiple layers, the thicknesses of the respective resin layers may be the same or different, but it is preferable that the thicknesses of the respective resin layers are the same. Furthermore, when the resin layer is disposed on both sides of the glass layer or is made of multiple layers, the respective resin layers may be made of the same resin or a resin having the same properties, or may be made of different resins, but it is preferable that the respective resin layers are made of the same resin. Therefore, it is particularly preferable that the respective resin layers are made of the same resin and have the same thickness. With such a configuration, even if heat treatment is performed, thermal stress is evenly applied to both sides of the glass layer, so that warping is extremely unlikely to occur.
[0082] The elastic modulus of the resin layer at 25° C. is not particularly limited and may be appropriately selected depending on the purpose, but is preferably 1.5 GPa to 10 GPa, more preferably 1.7 GPa to 8 GPa, and even more preferably 1.9 GPa to 6 GPa. When the elastic modulus of the resin layer at 25° C. is 1.5 GPa to 10 GPa, even if the glass layer is made thin, the resin layer relieves local stress in the tearing direction to defects during deformation, making it difficult for cracks or breakage to occur in the glass layer.
[0083] The light transmittance of the resin layer at a wavelength of 550 nm is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The light transmittance of the resin layer at a wavelength of 550 nm can be measured by a spectrophotometer (e.g., U-4100, manufactured by Hitachi, Ltd.).
[0084] <Other layers> The laminate may further include other layers, if necessary, in addition to the glass layer and the resin layer. Examples of the other layers in the laminate include a coupling agent layer, an adhesive layer, a transparent conductive layer, and a hard coat layer.
[0085] <<Coupling agent layer>> The coupling agent layer is preferably a layer disposed between the glass layer and the resin layer, and more preferably a layer in contact with the glass layer. The coupling agent layer can be formed, for example, by curing a coupling agent on the glass layer.
[0086] The coupling agent constituting the coupling agent layer is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include amino group-containing coupling agents, epoxy group-containing coupling agents, epoxy group-terminated coupling agents, isocyanate group-containing coupling agents, vinyl group-containing coupling agents, mercapto group-containing coupling agents, (meth)acryloxy group-containing coupling agents, etc. These may be used alone or in combination of two or more.
[0087] In the embodiment of the present invention, the term "(meth)acryloxy group" means an "acryloxy group" or a "methacryloxy group".
[0088] When the resin layer contains a thermoplastic resin having an ester bond (for example, at least one of thermoplastic resin (A) and thermoplastic resin (B)), the coupling agent constituting the coupling agent layer is preferably an amino group-containing coupling agent, an epoxy group-containing coupling agent, or an isocyanate group-containing coupling agent. The substitution position of the substituent possessed by these coupling agents may be the terminal of the molecule, or may not be the terminal. When a resin layer containing a thermoplastic resin having an ester bond and a glass layer are arranged only through a coupling agent layer formed by such a coupling agent (i.e., without an adhesive layer), the resin layer containing a thermoplastic resin having an ester bond can be firmly adhered to the glass layer through the coupling agent layer. It is presumed that the amino group, epoxy group, or isocyanate group in the coupling agent chemically bonds or interacts with the resin layer, and the silyl group in the coupling agent can be chemically bonded (typically, covalently bonded) to a substituent possessed by the glass layer (for example, a hydroxyl group). As a result, it is considered that the above-mentioned strong adhesion can be obtained.
[0089] When the resin layer contains a thermoplastic resin having a hydroxyl group (for example, thermoplastic resin (C)), the coupling agent constituting the coupling agent layer is preferably an epoxy group-terminated coupling agent. When a resin layer containing a thermoplastic resin having a hydroxyl group and a glass layer are arranged only through a coupling agent layer formed by such a coupling agent (i.e., without an adhesive layer), the resin layer containing a thermoplastic resin having a hydroxyl group can be firmly adhered to the glass layer through the coupling agent layer. It is presumed that the epoxy group in the coupling agent chemically bonds or interacts with the resin layer, and the silyl group in the coupling agent can be chemically bonded to a substituent (for example, a hydroxyl group) of the glass layer. As a result, it is believed that the above-mentioned strong adhesion can be obtained.
[0090] Examples of the amino group-containing coupling agent include alkoxysilanes having an amino group and halogenated silanes having an amino group, with alkoxysilanes having an amino group being preferred.
[0091] Specific examples of alkoxysilanes having an amino group include 3-aminopropyltrimethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropyldimethylmethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropylmethyldimethoxysilane, 6-aminohexyltrimethoxysilane, 6-aminohexyltriethoxysilane, 11-aminoundecyltrimethoxysilane, 11-aminoundecyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, and the like.
[0092] Specific examples of halogenated silanes having an amino group include 3-aminopropyltrichlorosilane, 3-aminopropylmethyldichlorosilane, 3-aminopropyldimethylchlorosilane, 6-aminohexyltrichlorosilane, and 11-aminoundecyltrichlorosilane.
[0093] Specific examples of epoxy group-containing coupling agents and epoxy group-terminated coupling agents include 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane.
[0094] A specific example of an isocyanate group-containing coupling agent is 3-isocyanatepropyltriethoxysilane.
[0095] Specific examples of vinyl group-containing coupling agents include vinyltrichlorosilane, vinyltris(β-methoxyethoxy)silane, vinyltriethoxysilane, vinylmethoxysilane, and γ-methacryloxypropyltrimethoxysilane.
[0096] Specific examples of mercapto group-containing coupling agents include mercaptomethyldimethylethoxysilane, (mercaptomethyl)methyldiethoxysilane, γ-mercaptopropylmethyldimethoxysilane, γ-mercaptopropyltrimethoxysilane, and γ-mercaptopropyltriethoxysilane.
[0097] Specific examples of the (meth)acryloxy group-containing coupling agent include γ-(meth)acryloxypropyltrimethoxysilane, γ-(meth)acryloxypropyltriethoxysilane, γ-(meth)acryloxypropylmethyldimethoxysilane, and γ-(meth)acryloxypropylmethyldiethoxysilane.
[0098] The coupling agent may be one synthesized by a known method, or a commercially available product may be used.
[0099] Examples of commercially available amino group-containing coupling agents include those manufactured by Shin-Etsu Chemical Co., Ltd. under the trade names "KBM-602" (N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane), "KBM-603" (N-2-(aminoethyl)-3-aminopropyltrimethoxysilane), "KBE-603" (N-2-(aminoethyl)-3-aminopropyltriethoxysilane), "KBM-903" (3-aminopropyltrimethoxysilane), "KBE-903" (3-aminopropyltriethoxysilane), "KBM-573" (N-phenyl-3-aminopropyltrimethoxysilane), and "KBE-9103" (3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine).
[0100] Examples of commercially available epoxy group-containing coupling agents (and epoxy group-terminated coupling agents) include those manufactured by Shin-Etsu Chemical Co., Ltd., such as those under the trade name "KBM-303" (2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane), "KBM-403" (3-glycidoxypropyltrimethoxysilane), "KBE-402" (3-glycidoxypropylmethyldiethoxysilane), and "KBE-403" (3-glycidoxypropyltriethoxysilane).
[0101] An example of a commercially available isocyanate group-containing coupling agent is the product name "KBE-9007" (3-isocyanatepropyltriethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd.
[0102] The average thickness of the coupling agent layer is not particularly limited as long as it does not impair the effects of the present invention and can be appropriately selected depending on the purpose, but is preferably 0.001 μm to 10 μm, more preferably 0.001 μm to 2 μm.
[0103] <<adhesive layer>> The adhesive layer is preferably a layer for bonding between the glass layer and the resin layer. The laminate in the embodiment of the present invention may further include a coupling agent layer between the glass layer and the adhesive layer or between the adhesive layer and the resin layer.
[0104] The material constituting the adhesive layer is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include curable resins that are cured by heat or active energy rays. Specific examples of such resins include cyclic ethers having an epoxy group, a glycidyl group, or an oxetanyl group, silicone resins, acrylic resins, and mixtures thereof.
[0105] The adhesive layer may contain a coupling agent. When the adhesive layer contains a coupling agent, the adhesiveness to the glass layer and / or the resin layer (when the laminate has a coupling agent layer, the coupling agent layer and / or the resin layer) may be improved.
[0106] The average thickness of the adhesive layer is not particularly limited as long as it does not impair the effects of the present invention, and can be appropriately selected depending on the purpose, but is preferably 10 μm or less, more preferably 0.01 μm to 10 μm, and even more preferably 0.1 μm to 7 μm. When the average thickness of the adhesive layer is 10 μm or less, excellent adhesion between the glass layer and the resin layer can be achieved without impairing the flexibility of the laminate.
[0107] <<Transparent conductive layer>> The transparent conductive layer is preferably disposed on the resin layer on the side opposite to the side on which the glass layer is disposed. The transparent conductive layer can function as an electrode or an electromagnetic wave shield when the laminate according to the embodiment of the present invention is used as a substrate for a display element or a solar cell.
[0108] The material constituting the transparent conductive layer is not particularly limited as long as it has conductivity and can be appropriately selected depending on the purpose, and examples thereof include metals such as copper and silver, metal oxides such as indium tin oxide (ITO) and indium zinc oxide (IZO), conductive polymers such as polythiophene and polyaniline, compositions containing carbon nanotubes, etc. These may be used alone or in combination of two or more.
[0109] The average thickness of the transparent conductive layer is not particularly limited as long as it does not impair the effects of the present invention, and can be appropriately selected depending on the purpose.
[0110] <<Hard coat layer>> The hard coat layer is preferably disposed on the resin layer on the side opposite to the side on which the glass layer is disposed. The hard coat layer has the function of imparting chemical resistance, scratch resistance, and surface smoothness to the laminate according to the embodiment of the present invention.
[0111] The material constituting the hard coat layer is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include epoxy resins, acrylic resins, silicone resins, and mixtures thereof. These may be used alone or in combination of two or more. Among these, epoxy resins having excellent heat resistance are preferred. The hard coat layer can be obtained by curing these resins with heat or active energy rays.
[0112] <Manufacturing method> The method for producing the laminate in the embodiment of the present invention is not particularly limited and may be appropriately selected depending on the purpose. Examples of the method include a method in which a resin layer is formed on a glass layer by solution coating to obtain a laminate (hereinafter, sometimes referred to as "Production Method Example 1"), and a method in which a resin layer is formed by adhering a resin film on a glass layer to obtain a laminate (hereinafter, sometimes referred to as "Production Method Example 2").
[0113] <<Production Method Example 1>> The method for forming a resin layer on a glass layer by solution coating to obtain a laminate preferably includes a coating step of coating one or both sides of the glass layer with a solution containing a material for forming the resin layer to form a coating layer, a drying step of drying the coating layer, and a heat treatment step of heat treating the dried coating layer to form a resin layer, and more preferably includes a coupling treatment step of subjecting the surface of the glass layer to a coupling treatment. The material for forming the resin layer used here is as described in the <Resin Layer> section above.
[0114] - Coating process - The coating solvent used in the coating process is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include halogen-based solvents such as methylene chloride, ethylene chloride, chloroform, carbon tetrachloride, and trichloroethane; aromatic solvents such as toluene, benzene, and phenol; cellosolve-based solvents such as methyl cellosolve and ethyl cellosolve; ether-based solvents such as propylene glycol monomethyl ether and ethylene glycol monoisopropyl ether; and ketone-based solvents such as methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone. These may be used alone or in combination of two or more. Among these, halogen-based solvents, aromatic solvents, cellosolve-based solvents, and ether-based solvents are preferred as coating solvents used in the coating process because they can sufficiently maintain the adhesion between the resin layer and the glass layer even under high temperature and high humidity conditions and can obtain a laminate with excellent durability and reliability.
[0115] The method for applying the solution containing the material that constitutes the resin layer is not particularly limited and can be appropriately selected depending on the purpose. Examples of the method include coating methods such as air doctor coating, blade coating, knife coating, reverse coating, transfer roll coating, gravure roll coating, kiss coating, cast coating, spray coating, slot orifice coating, calendar coating, electrodeposition coating, dip coating, and die coating; and printing methods such as letterpress printing methods such as flexographic printing, intaglio printing methods such as direct gravure printing and offset gravure printing, lithographic printing methods such as offset printing, and stencil printing methods such as screen printing.
[0116] -Drying process- As the drying step, any appropriate drying method (for example, natural drying, air drying, heat drying) can be adopted. In the case of heat drying, the drying temperature is preferably 100° C. to 200° C., and the drying time is preferably 1 minute to 10 minutes.
[0117] -Heat treatment process- Any appropriate heat treatment method can be adopted for the heat treatment step, but the heat treatment temperature is preferably 100° C. to 300° C., and the heat treatment time is preferably 5 minutes to 45 minutes. When the laminate in the embodiment of the present invention has a coupling agent layer, the heat treatment step can chemically bond or interact with the coupling agent and the resin contained in the resin layer.
[0118] -Coupling processing process- It is more preferable to include a coupling treatment step of subjecting the surface of the glass layer to a coupling treatment before the coating step. By carrying out the coupling treatment to form a coupling agent layer on the surface of the glass layer, the resin layer can be firmly adhered to the glass layer via the coupling agent layer. The material constituting the coupling agent layer used here is as described in the above item <Coupling Agent Layer>.
[0119] As the method for the coupling treatment, any appropriate method can be adopted, specifically, for example, a method in which a solution of a coupling agent is applied to the surface of the glass layer, and then the applied solution is subjected to a heat treatment.
[0120] The solvent used in preparing the coupling agent solution is not particularly limited as long as it is a solvent that does not react with the coupling agent, and any appropriate solvent can be used. Specific examples of the coupling agent solution include aliphatic hydrocarbon solvents such as hexane and hexadecane; aromatic solvents such as benzene, toluene, and xylene; halogenated hydrocarbon solvents such as methylene chloride and 1,1,2-trichloroethane; ether solvents such as tetrahydrofuran and 1,4-dioxane; alcohol solvents such as methanol and propanol; ketone solvents such as acetone and 2-butanone, and water. These may be used alone or in combination of two or more.
[0121] Any appropriate heat treatment method may be adopted for the heat treatment in the coupling treatment, but the heat treatment temperature is preferably 50° C. to 150° C., and the heat treatment time is preferably 1 minute to 10 minutes. The heat treatment can chemically bond the coupling agent to the glass layer surface.
[0122] <<Production Method Example 2>> In a method of forming a resin layer by adhering a resin film onto a glass layer to obtain a laminate, the resin layer may be formed by adhering a commercially available resin film to the surface of the glass layer, or the resin layer may be formed by applying a resin solution to any suitable substrate to form a resin film, and then transferring the resin film to the surface of the glass layer to adhere the glass layer and the resin film to each other.
[0123] In addition, before the resin film is attached, the surface of the glass layer may be subjected to a corona treatment, a plasma treatment, an excimer treatment, a frame treatment, or the like to modify the surface of the glass layer, or the glass layer may be subjected to a coupling treatment. The above-mentioned methods may be adopted as the coupling treatment method. Among these, the corona treatment is preferable in that reactive functional groups are generated on the surface of the glass layer, improving the adhesion with the resin layer, and foreign matter on the surface of the glass layer is removed by the ashing effect, and surface unevenness is reduced, so that a laminate having excellent appearance characteristics can be produced.
[0124] The resin film may be annealed before or after being attached to the glass layer. By performing the annealing treatment, impurities such as residual solvent and unreacted monomer components can be efficiently removed. The temperature and time of the annealing treatment are not particularly limited and can be appropriately selected depending on the purpose, but the temperature is preferably 100°C to 200°C, and the time is preferably 5 minutes to 20 minutes.
[0125] The resin film may be attached to the surface of the glass layer via an adhesive layer. The adhesive layer may be formed on the resin film and then attached to the surface of the glass layer, or the adhesive layer may be formed on the glass layer and then the resin film may be attached.
[0126] Examples of the method for forming the adhesive layer include a method in which a thermosetting resin or an active energy ray curable resin is applied to the surface of a glass layer or a resin film, the glass layer and the resin film are then attached, and the thermosetting resin or the active energy ray curable resin is then cured by ultraviolet light irradiation or heat treatment. The irradiation conditions for ultraviolet light irradiation are not particularly limited, but it is preferable that the irradiation cumulative light amount is 100 mJ / cm. 2 ~2,000mJ / cm 2 and the irradiation time is preferably 5 to 30 minutes. There are no particular limitations on the conditions for the heat treatment, but it is preferable that the heating temperature is 100°C to 200°C and the heating time is 5 to 30 minutes. After the thermosetting resin or active energy ray curable resin is applied to the surface of the glass layer or the resin film, the thermosetting resin or active energy ray curable resin may be semi-cured before the glass layer and the resin film are attached. There are no particular limitations on the conditions for semi-curing, but it is preferable that the heating temperature is 100°C to 200°C and the heating time is 5 to 30 minutes. 2 ~1,000mJ / cm 2 This can be done by irradiating the sample with ultraviolet light for 1 to 60 seconds.
[0127] Hereinafter, examples of the configuration of the laminate according to the embodiment of the present invention will be specifically described with reference to the drawings.
[0128] [[Configuration Example 1]] 1 is a schematic cross-sectional view showing an example of a laminate according to an embodiment of the present invention. The laminate 100a has a glass layer 10 and resin layers 11, 11' arranged on one surface or both surfaces, preferably both surfaces, of the glass layer 10.
[0129] [[Configuration Example 2]] 2 is a schematic cross-sectional view showing another example of a laminate according to an embodiment of the present invention. The laminate 100b differs from the first embodiment in that it further includes coupling agent layers 12, 12' between the glass layer 10 and the resin layers 11, 11'.
[0130] [[Configuration Example 3]] 3 is a schematic cross-sectional view showing another example of a laminate in an embodiment of the present invention. The laminate 100c differs from the first exemplary embodiment in that it further includes adhesive layers 13, 13′ between the glass layer 10 and the resin layers 11, 11′.
[0131] [[Configuration Example 4]] 4 is a schematic cross-sectional view showing another example of a laminate according to an embodiment of the present invention. The laminate 100d includes a glass layer 10, and coupling agent layers 12, 12', adhesive layers 13, 13', and resin layers 11, 11' arranged in this order on one or both surfaces, preferably both surfaces, of the glass layer 10.
[0132] In the laminate in the embodiment of the present invention, the glass layer and the resin layer may be arranged through a coupling agent layer as shown in FIG. 2 (glass layer / coupling agent layer / resin layer), or may be arranged through an adhesive layer as shown in FIG. 3 (glass layer / adhesive layer / resin layer). The laminate of the present invention may have a coupling agent layer and an adhesive layer as shown in FIG. 4, and the glass layer, the coupling agent layer, the adhesive layer, and the resin layer may be arranged in this order. Preferably, the coupling agent layer is formed directly on the glass layer. More preferably, the glass layer and the resin layer are arranged only through the coupling agent layer (glass layer / coupling agent layer / resin layer). With such a configuration, the glass layer and the resin layer can be firmly adhered to each other, so that a laminate having excellent dimensional stability, suppressing warping, and being less susceptible to crack development can be obtained.
[0133] The coupling agent layer is preferably chemically bonded (typically, covalently bonded) to the glass layer, so that a laminate having excellent adhesion between the glass layer and the coupling agent layer can be obtained.
[0134] The resin layer or adhesive layer is preferably bonded or interacts with the coupling agent layer by a chemical bond (typically, a covalent bond), resulting in a laminate having excellent adhesion between the coupling agent layer and the resin layer or adhesive layer.
[0135] <Application> The laminate according to the embodiment of the present invention can be suitably used as a substrate for nanoimprinting.
[0136] (Optical components) The optical component according to the embodiment of the present invention includes the laminate according to the embodiment of the present invention, and further includes other members as necessary. The laminate according to the embodiment of the present invention is as described in the section (Laminate).
[0137] <Other materials> There are no particular limitations on the other members in the optical component according to the embodiment of the present invention, so long as they do not impair the effects of the present invention, and examples of such members include well-known members that are commonly used in optical components.
[0138] <Manufacturing method> The method for producing the optical component according to the embodiment of the present invention is not particularly limited as long as the laminate according to the embodiment of the present invention is used, but the optical component is preferably produced by the method for producing the optical component according to the embodiment of the present invention described below.
[0139] <Application> The optical component according to the embodiment of the present invention can be suitably used in a display element or a solar cell. Examples of the display element include a liquid crystal display, a plasma display, and an organic electroluminescence display.
[0140] (Imprint method) The imprinting method in an embodiment of the present invention includes a transfer step of pressing a concave-convex portion of an imprint mold structure having a concave-convex portion against a surface of a resin layer of a laminate in an embodiment of the present invention opposite to a surface on which a glass layer is disposed, and transferring a concave-convex pattern based on the concave-convex portion of the imprint mold structure to the resin layer, and further includes other steps such as a curing step and a demolding step, as necessary.
[0141] <Transfer process> The transfer step is a step of pressing the concave-convex portion of an imprint mold structure having a concave-convex portion against the surface of the resin layer of the laminate in an embodiment of the present invention opposite to the surface on which the glass layer is disposed, thereby transferring a concave-convex pattern based on the concave-convex portion of the imprint mold structure to the resin layer.
[0142] The imprinting mold structure having the concave and convex portions is not particularly limited, and any known imprinting mold structure can be used, such as a master for bit patterned media (BPM) having fine concave and convex portions.
[0143] There are no particular limitations on the width or diameter and depth of the concave and convex portions in the imprint mold structure having concave and convex portions, and these can be appropriately selected depending on the type of optical component to be manufactured.
[0144] When the material constituting the resin layer is a thermoplastic resin, in the transfer step, heat is applied at a temperature suited to the thermoplastic resin, and the imprint mold structure having the concave-convex portions is pressed in a softened state, thereby allowing the concave-convex pattern based on the concave-convex portions of the imprint mold structure to be suitably transferred to the resin layer. When the material constituting the resin layer is a curable resin that is cured by heat or active energy rays, the imprint mold structure having the concave-convex portions is pressed in an uncured state prior to application of heat or active energy rays, allowing the concave-convex pattern based on the concave-convex portions of the imprint mold structure to be suitably transferred to the resin layer.
[0145] <Curing process> The curing step is a step of curing the resin constituting the resin layer in a state in which the imprint mold structure having the concave-convex portions is pressed against the resin layer of the laminate in an embodiment of the present invention.
[0146] The curing method is not particularly limited and can be appropriately selected depending on the type of resin constituting the resin layer. For example, a method of curing with heat or active energy rays can be mentioned.
[0147] <Mold release process> The demolding step is a step of separating the uneven imprint mold structure from the resin layer after the curing step, thereby separating the resin layer from the uneven imprint mold structure, and obtaining a resin layer to which the uneven pattern based on the unevenness of the uneven imprint mold structure is transferred.
[0148] (Manufacturing method for optical components) A method for manufacturing an optical component in an embodiment of the present invention includes a transfer step of pressing a concave-convex portion of an imprint mold structure having a concave-convex portion against a surface of a resin layer of a laminate in an embodiment of the present invention opposite to a surface on which a glass layer is disposed, and transferring a concave-convex pattern based on the concave-convex portion of the imprint mold structure to the resin layer, and further includes other steps such as a curing step and a demolding step, as necessary.
[0149] The imprint method according to the embodiment of the present invention can be suitably applied to the method for manufacturing an optical component according to the embodiment of the present invention. Therefore, the transfer step, curing step, and demolding step in the method for manufacturing an optical component according to the embodiment of the present invention can be performed in the same manner as the transfer step, curing step, and demolding step in the method for manufacturing an optical component in the imprint method according to the embodiment of the present invention.
[0150] The optical component manufactured by the method for manufacturing an optical component according to the embodiment of the present invention can be suitably used as a display element or a solar cell. Examples of the display element include a liquid crystal display, a plasma display, and an organic EL display. Since the laminate according to the embodiment of the present invention is suppressed in warping, an optical component having excellent characteristics can be obtained. EXAMPLES
[0151] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these examples in any way.
[0152] Example 1 In Example 1, a laminate 100e having the cross-sectional structure shown in FIG. 5 was produced by the following method.
[0153] A square inorganic glass (OA-10G, Nippon Electric Glass Co., Ltd.) having a thickness of 100 μm, length of 6 cm and width of 6 cm was used as the glass layer, and one surface of the glass layer was washed with isopropyl alcohol and then subjected to a corona treatment.
[0154] An adhesive (epoxy resin (Celloxide 2021P, manufactured by Daicel Chemical Industries, Ltd.)) was applied to the entire surface (corona-treated surface) of the glass layer 10 so that the average thickness after curing was 3 μm. Next, a square polyimide (PI) film (Upilex (registered trademark) 25S, manufactured by UBE Corporation) 11 with an average thickness of 25 μm, length of 6 cm, and width of 6 cm was laminated on the adhesive-coated surface. Next, ultraviolet light (wavelength: 365 nm, intensity: 1,000 mJ / cm) was applied from a high-pressure mercury lamp. 2 The adhesive was irradiated with the above light from the glass layer side to harden the adhesive and form an adhesive layer 13. This resulted in a laminate 100e in which the glass layer 10, the adhesive layer 13, and the resin layer 11 were laminated in this order.
[0155] Example 2 A laminate was formed in the same manner as in Example 1, except that a square polyimide (PI) film (Upilex (registered trademark) 25S, manufactured by UBE Corporation) having an average thickness of 25 μm and a length of 6 cm and a width of 6 cm was used as a square PET film (Cosmoshine (registered trademark) A4360 38 μm, manufactured by Toyobo Co., Ltd.) having an average thickness of 38 μm and a length of 6 cm and a width of 6 cm.
[0156] Example 3 A laminate was formed in the same manner as in Example 1, except that a square polyimide (PI) film (Upilex (registered trademark) 25S, manufactured by UBE Corporation) having an average thickness of 25 μm and a length of 6 cm and a width of 6 cm was used as a square PET film (Lumirror (registered trademark) #16-F68, manufactured by Toray Industries, Inc.) having an average thickness of 16 μm and a length of 6 cm and a width of 6 cm.
[0157] Example 4 A laminate was formed in the same manner as in Example 1, except that a square polyimide (PI) film (Upilex (registered trademark) 25S, manufactured by UBE Corporation) having an average thickness of 25 μm and a length of 6 cm and a width of 6 cm was used as a square PET film (Lumirror (registered trademark) #25-F66, manufactured by Toray Industries, Inc.) having an average thickness of 25 μm and a length of 6 cm and a width of 6 cm.
[0158] Example 5 A laminate was formed in the same manner as in Example 1, except that a square polyimide (PI) film (Upilex (registered trademark) 25S, manufactured by UBE Corporation) having an average thickness of 25 μm and a length of 6 cm and a width of 6 cm was used as a square PET film (Lumirror (registered trademark) #6-F557, manufactured by Toray Industries, Inc.) having an average thickness of 6 μm and a length of 6 cm and a width of 6 cm.
[0159] Comparative Example 1 A laminate was formed in the same manner as in Example 1, except that a square polyimide (PI) film (Upilex (registered trademark) 25S, manufactured by UBE Corporation) having an average thickness of 25 μm and a length of 6 cm and a width of 6 cm was used as a square PET film (Cosmoshine (registered trademark) A4360 100 μm, manufactured by Toyobo Co., Ltd.) having an average thickness of 100 μm and a length of 6 cm and a width of 6 cm.
[0160] <Warpage evaluation> For each of the laminates formed in Examples 1 to 5 and Comparative Example 1, evaluation of warpage was performed by digital image correlation analysis (DIC analysis). Specifically, a spray (water-based lacquer spray, manufactured by Sunday Paint Co., Ltd.) was sprayed on the exposed surface of the resin layer 11 of the laminate 100e shown in FIG. 5 to prepare a measurement sample having a random granular pattern (speckle pattern) on the surface. The measurement sample was placed in an oven having an observation window. At this time, the surface of the laminate having the speckle pattern was arranged so that it was on the observation window side. A thermocouple was also installed near the measurement sample in the oven. Next, from the outside of the observation window, a twin-lens camera having an LED lamp was used to take a subset of the entire area of the surface of the laminate, which was 6 cm long and 6 cm wide, while irradiating the LED thereon, and this was taken as "Image 1" of the state of the laminate before heating. Next, the oven was heated, and when the thermocouple displayed 60°C, the subset on the surface of the laminate was taken from the outside of the observation window while irradiating the LED thereon, and this was taken as "Image 2" of the state of the laminate after heating.
[0161] The deformation measurement and strain analysis device (StarinMaster, manufactured by LaVision) was used to analyze the x- and y-directional distortions and the z-directional displacement of the captured images 1 and 2. As shown in FIG. 6, the surface of the laminate on which the speckle pattern was applied (the area shown by the solid line in FIG. 6) was divided into nine parts as shown by the dotted line in FIG. 6, and the maximum value of the z-directional displacement of each of the nine divided parts was calculated for nine points. The maximum value among the maximum values of the z-directional displacement of the nine points was taken as the maximum z-directional displacement of the measurement sample at 60°C. The larger the maximum z-directional displacement, the larger the thermal warpage of the laminate. The results of the maximum z-directional displacement are shown in Table 1 below as "maximum thermal warpage." In addition, a photograph showing the distortion of image 2 based on a color meter is shown in FIG. 8.
[0162] [Table 1]
[0163] Comparing Examples 1 to 5 with Comparative Example 1, the laminates of Examples 1 to 5, which had an average thickness ratio (resin layer / glass layer) of less than 0.9, had a suppressed maximum thermal warpage. In addition, the thinner the resin layer was, the greater the suppression effect of the maximum thermal warpage.
[0164] The aspects of the present invention include, for example, the following. <1> A glass layer and a resin layer disposed on at least one surface of the glass layer, The laminate is characterized in that the ratio of the average thickness of the resin layer to the average thickness of the glass layer (resin layer / glass layer) is less than 0.9. <2> The absolute value of the maximum thermal warpage in the thickness direction of the laminate at 60° C. is less than 2 mm when measured by a digital image correlation method. <1> 1. The laminate according to claim 1 . <3> The average thickness of the glass layer is 200 μm or less. <1> or <2> 1. The laminate according to claim 1 . <4> It is used as a substrate for imprinting. <1> from <3> The laminate according to any one of claims 1 to 5, <5> The above <1> from <4> 1. An optical component comprising the laminate according to claim 1. <6> The uneven portion of the imprint mold structure having the uneven portion is <1> from <5> a resin layer of the laminate according to any one of claims 1 to 5, wherein the resin layer is pressed against a surface opposite to a surface on which a glass layer is disposed, thereby transferring a concave-convex pattern based on the concave-convex portion of the imprint mold structure to the resin layer. <7> The uneven portion of the imprint mold structure having the uneven portion is <1> from <5> a resin layer of the laminate according to any one of claims 1 to 5, wherein the resin layer is pressed against a surface opposite to a surface on which a glass layer is disposed, thereby transferring a concave-convex pattern based on the concave-convex portion of the imprint mold structure to the resin layer.
[0165] As described above, the present invention has been described based on specific embodiments and examples, but these embodiments and examples are presented only as examples, and the present invention is not limited to the embodiments and examples. The embodiments can be implemented in various other forms, and various combinations, omissions, substitutions, additions, modifications, etc. can be made without departing from the gist of the invention. These embodiments and their modifications are included in the scope and gist of the invention, and are included in the scope of the invention and its equivalents described in the claims. [Industrial Applicability]
[0166] The laminate according to the embodiment of the present invention can be suitably used as a substrate for nanoimprinting. Furthermore, an optical component having the laminate according to the embodiment of the present invention can be widely used in display elements such as liquid crystal displays, organic EL displays, and plasma displays, and solar cells. [Explanation of symbols]
[0167] 100a, 100b, 100c, 100d, 100e … laminate 10 … Glass layer 11, 11' ... resin layer 12, 12' ... coupling agent layer 13, 13'... Adhesive layer
Claims
1. A glass layer and a resin layer disposed on at least one surface of the glass layer, A laminate, wherein a ratio of an average thickness of the resin layer to an average thickness of the glass layer (resin layer / glass layer) is less than 0.
9.
2. 2. The laminate according to claim 1, wherein the absolute value of the maximum thermal warpage in the thickness direction of the laminate at 60° C. is less than 2 mm when measured by a digital image correlation method.
3. The laminate according to claim 1 or 2, wherein the glass layer has an average thickness of 200 μm or less.
4. Used as a substrate for imprinting. The laminate according to claim 1 or 2.
5. An optical component comprising the laminate according to claim 1 or 2.
6. 3. An imprinting method comprising a transfer step of pressing a concave-convex portion of an imprint mold structure having a concave-convex portion against a surface of a resin layer of the laminate according to claim 1 or 2 opposite to a surface on which a glass layer is disposed, and transferring a concave-convex pattern based on the concave-convex portion of the imprint mold structure to the resin layer.
7. 3. A method for producing an optical component, comprising: a transfer step of pressing a concave-convex portion of an imprint mold structure having a concave-convex portion against a surface of a resin layer of the laminate according to claim 1 or 2 opposite to a surface on which a glass layer is disposed, and transferring a concave-convex pattern based on the concave-convex portion of the imprint mold structure to the resin layer.
Citation Information
Patent Citations
Flexible substrate for organic device, and organic device and production of the same
JP1999329715A
Photosensitive resin compositions, photosensitive element containing the same, process for producing resist pattern, and process for producing printed circuit board
WO2001022165A1